Impacts of Gestational Diabetes Mellitus on the Mother and the Neonate A Descriptive Study (Bangladesh Journal of Anatomy, 2011)
Context: Pregnancy complicated by diabetes is a significant medical problem not only affecting maternal health, but also jeopardizing fetal normalcy. Gestational diabetes mellitus (GDM) is a common metabolic disorder that frequently causes maternal and fetal complications. The present study was done to see the impacts of GDM on mother and neonate. Study design: Cross sectional descriptive study. Place and period of study: Department of Anatomy Chittagong Medical College, Chittagong. From May 2006 to April 2007. Material: Total number of subjects were seventy, of which 35 were non diabetic pregnant Bangladeshi Bengoli mother (Control group) and 35 were mothers with GDM (GDM group). All GDM mother were under insulin therapy having HbA1C within 6.5% to 6.8%. Method: Relevant data of the mother (Age, weight, gestational period, parity) and the neonate (birth weight, APGAR score) were collected by taking history and hospital record book. APGAR score at 1st minute was taken from the records as determined by the on-duty Anesthetist. Result: Among the maternal and neonatal variables the mean age, gestational period and parity of the mother were significantly higher in the GDM group than in the Control group (P = 0.01, P = 0.00, P = 0.01 respectively). The mean weight of the mother and the mean neonatal birth weight were also higher in the GDM group, but not differ significantly. The mean APGAR score was found to be slightly lower in the GDM group than in the Control group, but the difference was not significant from the statistical point of view. Conclusion: The present study shows that the GDM may have some adverse impacts on the mother and neonate. Further study with larger sample size having vigorous exclusion criteria is recommended. Key words: Gestatational Diabetes Mellitus (GDM); Mother; Neonate. DOI: 10.3329/bja.v8i2.7018Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 64-63